The powers of Aristotle's soul - Johansen, T. K. (Oxford : Oxford University Press, 2012)
Thomas Kjeller Johansen presents a new account of Aristotle's major work on psychology, the De Anima. He argues that Aristotle explains a variety of psychological phenomena by reference to the soul's capacities, and considers how Aristotle adopts and adapts this theory in his later works.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Aristotle; Psychology -- Early works to 1850.; Soul -- Early works to 1800.